2011
DOI: 10.1007/s00127-011-0385-5
|View full text |Cite
|
Sign up to set email alerts
|

Recall of recent and more remote depressive episodes in a prospective cohort study

Abstract: Reporting of depressive episodes diminishes with time, suggesting that retrospective assessment of such episodes may be vulnerable to inaccuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…The study also extends past research comparing estimates in adolescents and young adult samples 13,16 or limited to depression. 9-12 In our study, subjects were followed from an average age of 35 ± 13 to 59 ± 13 years and we evaluated several mental disorders. Nevertheless, our results are similar to those of the study by Moffit et al 13 who showed higher lifetime prevalence estimates of psychiatric diagnoses across ages 18 to 32 years, compared to retrospective assessments.…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study also extends past research comparing estimates in adolescents and young adult samples 13,16 or limited to depression. 9-12 In our study, subjects were followed from an average age of 35 ± 13 to 59 ± 13 years and we evaluated several mental disorders. Nevertheless, our results are similar to those of the study by Moffit et al 13 who showed higher lifetime prevalence estimates of psychiatric diagnoses across ages 18 to 32 years, compared to retrospective assessments.…”
Section: Commentsmentioning
confidence: 99%
“…With regard to depressive symptoms, for example, diminishing recall of past symptoms with time has been reported in a number of studies. 9-12 Retrospective evaluation may thus substantially underestimate or overestimate the true lifetime prevalence of mental disorders. Recently Moffit and colleagues 13 examined the potential impact of recall bias in epidemiologic studies by comparing estimates based on one-time retrospective reports and those based on reports over multiple interviews in the same cohort.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals also vary in their ability to recall details of diagnosis and treatment in an accurate manner. Gaps and inaccuracies in patient reports can arise from ordinary errors in comprehension, recall, and expression (Patten et al 2012;Redelmeier et al 2001;Simon et al 2012). More errors occur when the patient is recalling more distant events (Patten et al 2012;Simon et al 2012).…”
Section: Apa Practice Guidelinesmentioning
confidence: 99%
“…Gaps and inaccuracies in patient reports can arise from ordinary errors in comprehension, recall, and expression (Patten et al 2012;Redelmeier et al 2001;Simon et al 2012). More errors occur when the patient is recalling more distant events (Patten et al 2012;Simon et al 2012). Factors other than time may also play a role in these variations in recall (Leikauf et al 2013).…”
Section: Apa Practice Guidelinesmentioning
confidence: 99%